Design of Event-Triggered Secure Containment Controllers for Multi-Agent Systems over Signed Graphs - Zheng, Shaobo; Zhou, Lei (Circuits, systems, and signal processing, 2025)
This paper addresses the secure containment control problem for a class of discrete-time multi-agent systems with eavesdroppers under signed graphs, with a focus on the scenarios where the graphs are structurally balanced. In order to deal with the complexity caused by the network, two techniques are used. On one hand, an encryption-decryption algorithm is proposed to improve data security and reliability. On the other hand, an event-triggered mechanism is introduced with the objective of optimizing the allocation of channel resources and the Zeno behavior also can be avoided. The purpose of the addressed problem is to develop a distributed, event-triggered, secure control protocol that ensures the desired containment performance of the system. In comparison with existing protocols, the proposed containment control protocol considers several factors simultaneously, including containment behavior, cooperation-competition relationships, event-triggered conditions, and the encryption-decryption algorithm. Two examples are presented to demonstrate the effectiveness of the developed control protocol.